IMPLEMENTATION OF CHARACTER EDUCATION AT THE BASIC EDUCATION LEVEL: A SYSTEMATIC LITERATURE REVIEW - Abdillah, Lucky Rafli (Proceedings Series of Educational Studies, 2024)
Abstract Education is an important foundation in human life, as explained in Law No. 20 of 2003 concerning the National Education System, that "Education is a conscious and planned effort to create a learning atmosphere that allows students to actively develop their potential." Education plays an important role in the growth of the country, because good Human Resources (HR) will produce good output, thus encouraging the progress of the country. However, improving the quality of HR, especially in the field of education, still faces many challenges, one of which is the character of education. This study aims to explore the implementation of character education in elementary schools and the obstacles that hinder the process. The focus of the study includes two objectives: (1) understanding how character education is applied in elementary schools, and (2) identifying steps to overcome obstacles in its implementation. The method used is the Systematic Literature Review (SLR), which reviews various related literature. The results of the study show that character education can be implemented through three main environments: family, school, and community. Schools play a central role, with good management as the key to its success. However, there are various obstacles, both from internal factors of students such as motivation, and external factors such as limited facilities and lack of family and community support. Cooperation between schools, families and communities is essential to overcome these obstacles and support the implementation of effective character education.